(untitled) - Giddens, Anthony (New York, 1999)
In Anthony Giddens's Introduction to Sociology, students learn from a perspective unmatched by other texts: one that applies a global perspective to the core introductory topics and recognizes the field;'' historical foundations without losing sight of contemporary theory and research. Giddens builds the basic introductory material around several central themes-the changing world, the globalization of social life, life in other societies, history and gender-that provide students with a useful organizational structure to help them learn the multiplicity of idea and topics presented in the introductory course. With Giddens's Introduction to Sociology, students are given the necessary foundations to understand the changing world around them
Keywords: Sociology,Xã hội học